2021
DOI: 10.1088/1742-6596/2131/2/022057
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of a new method of transportation of viscous petroleum products at low air temperatures

Abstract: High viscosity petroleum products such as fuel oils and cracking residues are widely used as marine and boiler fuels both in Russia and in its exports. Conveying viscous petroleum products at low air temperatures has a high cost due to the unloading and cleaning processes of the transport tanks. Refined petroleum product cools and solidifies during transportation, becoming highly viscous, making it impossible to drain it without preheating to restore fluidity. Emerging difficulties are common to all countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It can be concluded that when TGC is suppressed, a liquid petroleum product will cool down as a quasisolid body by molecular thermal conductivity at λ VPP of about 0.12 W/m°C, and the temperature distribution in it will correspond to the picture shown in Fig. 2 [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Evaluation Of the Results Of Hydrodynamic Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that when TGC is suppressed, a liquid petroleum product will cool down as a quasisolid body by molecular thermal conductivity at λ VPP of about 0.12 W/m°C, and the temperature distribution in it will correspond to the picture shown in Fig. 2 [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Evaluation Of the Results Of Hydrodynamic Calculationsmentioning
confidence: 99%
“…The fi rst method is implemented in a specialized tank wagon, model 15-1566, for viscous liquid cargoes with a steam heating casing rigidly mounted on the bottom of the tank [7,19,20,24]. The model was developed back in the 1960s, has been modernized many times, and is now widely used (Fig.…”
Section: Obtaining the Stratified State Of Liquid Petroleum Fuelsmentioning
confidence: 99%